0459 Cardiovascular Dysfunctions Associated with Sleep-related Breathing Disturbances. (27th April 2018) - Palamarchuk, I S; Saad, M; Douglass, A B; Lee, E; Ray, L; BuJaki, B; Parvaresh, A; De Koninck, J; Robillard, R
Abstract: Introduction: Convincing evidence emphasizes cardiac arrhythmias and sleep-disordered breathing (SDB) as independent risk factors for stroke and cardiovascular mortality. Sleep research focused on acute cardiac events following respiratory disturbances (ACERD) may provide deeper insights into the link between nocturnal cardiovascular deterioration and central dysautonomia. We aimed to investigate ACERD occurrence across sleep stages in people with various degrees of SDB. Methods: Clinical polysomnography for 221 individuals with sleep complaints referred to a sleep clinic was analyzed to identify the co-occurrence of ACERD within hazard period of 90 seconds. Beside the apnea hypopnea index (AHI), a respiratory-cardiac index (RCI) was calculated as the total count of respiratory-to-cardiac events occurring during specific sleep stage divided by the number of minutes spent in the sleep stage. Results: People with low SDB (AHI<15) presented with higher RCI in rapid eye movement (REM) sleep than in non-REM sleep (t(176) = -2.6, p = 0.010), but no significant difference between REM and NREM RCI were found for those with higher SDB (AHI≥15). Higher RCI during REM correlated with higher sleep fragmentation (r = -0.14, p = 0.038). Higher RCI during NREM sleep correlated with older age (r = 0.22, p < 0.001) and higher sleep fragmentation (r = -0.29, p < 0.001). There was no significant correlation between RCI and body mass indexes, AHI or Epworth Sleepiness Scale scores. Conclusion: In mild SDB, REM associated breathing disruptions may have a stronger connection to acute cardiovascular dysregulation than those arising during NREM. In severe sleep apnea, ACERD may be more pervasive across sleep stages. Hypothetically, the interaction between SDB and cardiovascular regulation may be influenced by REM-specific autonomic sensitivity, but may further extend towards NREM dysautonomia as the severity of sleep apnea progresses. Further research is necessary to determine whether AHI modulates REM and NREM autonomic functions related to ACERD. Support (If Any): N/A.